2011
DOI: 10.1007/s00535-011-0458-y
|View full text |Cite
|
Sign up to set email alerts
|

The determination of GGT is the most reliable predictor of nonresponsiveness to interferon-alpha based therapy in HCV type-1 infection

Abstract: These findings prove the predictive sensitivity of GGT as an independent indicator of nonresponsiveness even at levels that are slightly above the normal range. This new predictive parameter may help to improve individualized therapy in HCV type-1 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 33 publications
(34 reference statements)
2
26
1
Order By: Relevance
“…Several investigators reported that increased γGT activity strongly associates with primary antiviral treatment failure [21,64,[67][68][69]. Weak trend of inverse SVR correlation with γGT activity was found in our study by univariate analysis too [OR 2.242 (0.956-5.259), p-0,063], but it was not confirmed by multivariate analysis.…”
Section: Discussioncontrasting
confidence: 83%
“…Several investigators reported that increased γGT activity strongly associates with primary antiviral treatment failure [21,64,[67][68][69]. Weak trend of inverse SVR correlation with γGT activity was found in our study by univariate analysis too [OR 2.242 (0.956-5.259), p-0,063], but it was not confirmed by multivariate analysis.…”
Section: Discussioncontrasting
confidence: 83%
“…Absence of association of gender and BMI with treatment outcomes was also shown in several large prospective studies [11,12,24]. It is also worth noting, that although 61% of our patients were overweight (BMI > 25 kg/m with other studies [17,33], which rendered differences statistically non-significant. Therefore, we agree with Navaneethan et al [35] in that the use of the above pre-treatment factors cannot accurately predict SVR in all patients.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, previous studies have shown that younger age (< 40 years), normal GGT level, high ALT level, normal platelet count, absence of cirrhosis, low viral load, virus genotype and Caucasian race were more probably associated with better treatment outcomes [11][12][13][14]17,33]. Also, as suggested by Marcellin et al [34], referring to the PROPHESYS database, a simple scoring system including such factors as age, BMI, viral load, platelet count, ALT level and ALT/AST ratio can help identify HCV-1b patients who can benefit from therapy with pegylated interferon and ribavirin.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory parameters such as the level of ALT and γ-GT are associated with treatment outcome after antiviral therapy irrespective of receiving either dual or triple therapy combinations [7,11,12,13,16]. None of these studies, however, reported a cutoff value for these two laboratory factors that define a successful treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In two prospective trials, serum ALT activity was not related to SVR. In contrast, in retrospective studies using multivariate multinomial logistic regression analysis, high ALT activity was associated with treatment outcome [7,11,12]. In addition, low pretreatment serum γ-glutamyltransferase (γ-GT) activity was found to be significantly and independently related to SVR in multivariate regression analyses [12,13].…”
Section: Introductionmentioning
confidence: 99%